Sofosbuvir/velpatasvir for the treatment of hepatitis C in pediatric patients. (3rd October 2021) - Rubino, Chiara; Trapani, Sandra; Indolfi, Giuseppe
ABSTRACT: Introduction : Sofosbuvir/velpatasvir is a combination of direct-acting antivirals with pangenotypic activity for treatment of chronic hepatitis C virus infection. It was approved in 2020 for use in children aged 6–17 years and in June 2021 by the United States Food and Drug Administration for the age group 3–5 years. Areas covered : A literature search of PUBMED and EMBASE was conducted on April 30th and updated on June 10th. Other citations were identified in references of available literature and from ClinicalTrials.gov. The aim of the present research was to outline and discuss the pharmacokinetics, clinical efficacy, tolerability and safety of sofosbuvir/velpatasvir, exploring its actual and potential use in children and adolescents with chronic hepatitis C virus infection. Expert opinion : Five combinations of direct-acting antivirals, of whom three with pangenotypic activity, are now approved for children. No major differences in efficacy and safety profile have been described. Limited access to treatment still is a major issue, especially in low and middle-income countries.